DEFINITION OF THE BOUNDARIES OF SURROUNDING TERRITORY EXISTING HOUSING - and (Municipal economy of cities. Series: «Economy science», 2013)
On the example of residential districts of Kharkov different periods shows the distribution of built-up area into separate sections - local area of each apartment building, set the size and boundaries of reserve land, offered their continued use.